PENGARUH CASH FLOW, LEVERAGE, SIZE OF FIRM, NET WORKING CAPITAL, CAPITAL EXPENDITURE, GROWTH OPPORTUNITY DAN VOLATILITY OF CASH FLOW TERHADAP KEBIJAKAN CASH HOLDING PERUSAHAAN (Studi Empiris pada Perusahaan Sub Sektor Industri Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Ginanjar Rizki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine and analyze the significance of the influence of cash flow, leverage, size of firm, net working capital, capital expenditure, growth opportunity, and volatility of cash flow on the cash holding policy of automotive and component companies listed in the Indonesia Stock Exchange. Research type of this study is explanatory research and data collection method is documentary. This study used data from annual reports of automotive and component companies published from 2010-2014. The source of data were obtained from IDX’s websites. The sample of this research is 9 companies. Data analysis used in this study are multiple linear regression and descriptive analysis. The results showed that the company's policy of cash holding is significantly affected by cash flow, size of firm, net working capital, capital expenditure and volatility of cash flow. Meanwhile, leverage and growth opportunity do not significantly affect the cash holding policy. Keywords: cash holding, cash flow, leverage, size of firm, net working capital, capital expenditure, growth opportunity, volatility of cash flow